Peran Tokoh Informal dalam Meningkatkan Mutu Pendidikan Umat di PP. An-Nuriyah Kaliwining Rambipuji Jember: The Role of Informal Leaders in Enhancing the Quality of Community Education at An-Nuriyah Islamic Boarding School, Kaliwining, Rambipuji, Jember - Sarwan Sarwan (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2006)
The low level of support and the limited participatory roles of informal leaders in educational development constitute a critical issue in Jember Regency. This research examines the strategic role of informal leaders as agents of social change to improve the quality of community education. The study aims to analyze the roles, strategies, and constraints of informal leaders at Annuriyah Islamic Boarding School in Kaliwining. A qualitative approach was employed, using observation, in-depth interviews, and document analysis. The findings reveal that informal leaders are directly involved in strengthening moral character, improving teacher quality, developing the curriculum, and building academic traditions within the pesantren. Externally, they contribute to community service, parent guidance, and economic empowerment. In conclusion, informal leaders significantly enhance educational quality through effective pesantren management and university partnerships. The study recommends local government policies that support pesantren education and increased community participation. Rendahnya dukungan dan peran partisipatif tokoh informal dalam pembangunan pendidikan menjadi isu krusial di Kabupaten Jember. Penelitian ini bertolak dari peran strategis tokoh informal sebagai agen perubahan sosial dalam meningkatkan mutu pendidikan umat. Tujuan penelitian adalah menganalisis peran, strategi, serta hambatan tokoh informal di Pondok Pesantren Annuriyah Kaliwining. Pendekatan kualitatif digunakan dengan teknik observasi, wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa tokoh informal terlibat langsung dalam penguatan akhlakul karimah, peningkatan kualitas sumber daya guru, pengembangan kurikulum, serta membangun tradisi akademik pesantren. Secara eksternal, mereka berperan dalam pengabdian masyarakat, pembinaan wali santri, dan pemberdayaan ekonomi. Kesimpulannya, tokoh informal berkontribusi signifikan melalui manajemen pesantren yang efektif dan kemitraan dengan perguruan tinggi. Rekomendasi penelitian ini adalah perlunya kebijakan pemerintah daerah yang berpihak pada pendidikan pesantren serta peningkatan partisipasi masyarakat.